Causes and Approaches Used in the Management of Truancy in Public Secondary Schools in Nyamira North District, Nyamira County, Kenya - Afande, Francis Ofunya (2015)
Purpose: The study sought to investigate the causes and approaches used in the management of truancy in Nyamira North district in Kenya. The study was guided by the following specific objectives: to analyze the school related causes of truancy in secondary schools in Nyamira North district; to assess home related causes of truancy in secondary schools in Nyamira North district; and to evaluate the approaches used in the management of truancy in secondary schools in Nyamira North district. Literature review on truancy was undertaken in order to provide a bridge and clear understanding of existing knowledge base in the problem area. Methods: The literature review is based on authoritative, recent, and original sources such as journals, books, thesis and academic projects. A descriptive survey was used to undertake the study. The method permits gathering of data from the respondents in natural settings. A census of 36 public secondary schools in Nyamira North District was undertaken. All the school principals participated in the study. In order to obtain data from the students, stratified random sampling was used, where by in each school, forms 1, 2, 3 and 4 were each represented by 8 students, selected at random. In total 36 Principals and 288 students participated in the study. A semi-structured questionnaire was used to collect primary data from the respondents in public secondary schools in Nyamira North District. Content analysis was employed for data pertaining to the profile of the respondents while data pertaining to the objectives of the study was analyzed by employing descriptive statistics. Statistical Package for Social Sciences (SPSS) was used in data entry and analysis. Results: The study findings showed that even though the main causes of truancy vary from study to study, a combination of home, school and individual factors may be involved. The main causal factors of truancy include individual factors, institutional factors, and family backgrounds and community factors. The individual factors include: anxiety and fear; poor social skills; low self – esteem; anti-social behavior; scholastic failure; learning problems; cognitive style; poor habits arising from initially legitimate reasons. The institutional factors include: dilapidated school building and poor facilities; school size; movement between classes during lesson changes; classroom management; bullying; educator-learner relationship; teaching or instructional approach. The family and community factors include: socio-economic status of parents; marital status of parents; poor involvement and supervision; peer influence; violence and drug use. The findings also show that the approaches used in the management of truancy in schools may be categorized into the following: personal traits, school aspects, community aspects and others. In view of the findings, the following recommendations were made: there is need for the management of schools to accord the students opportunities for connection and social bonding; there is need for the management of schools to emphasize students’ commitment in schools; the management of schools should endeavor to involve students in as many school activities as possible, including day-to-day management of the schools; and belief and values should be emphasized as they are often not formally written but serve as the moral conscience of the society that determines right from wrong. Keywords: Truancy, Public Secondary school